Contextual Effect of the Integrated Health Post (Posbindu) and Biopsychosocial Determinants of Tertiary Preventive Behavior in Patients with Hypertension - Very Retnowati; Pawito Pawito; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Tertiary prevention of hypertension is a preventive effort to make patients with hypertension do not have disabilities and further complications. It also improves the quality of life and makes life longer. The biopsychosocial aspect affects individuals in learning, doing, and maintaining certain behaviors based on social cognitive theory. This study aimed to analyze the biopsychosocial determinants of tertiary preventive behavior among patients with hypertension.Subjects and Method: This study was an analytical observational study with a cross-sectional design. The study was conducted at 25 Integrated Health Posts (Posbindu) in Sragen, Central Java. A sample of 200 hypertensive patients was selected by stratified random sampling. The dependent variable was the tertiary preventive behavior of hypertension. The independent variables were observational learning, role model, imitation, vicarious learning, reinforcement, self-efficacy, self-regulation, outcome expectation, and attitude. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression.Results: Hypertension preventive behavior increased with observational learning (b= 2.85; 95% CI= 0.17 to 5.53; p= 0.037), role model (b= 2.73; 95% CI =0.73 to 4.73; p=0.007), imitation (b= 3.46 ; 95% CI= 0.73 to 6.19; p= 0.013), vicarious learning (b= 2.54; 95% CI =0.16 to 4.93; p= 0.036), reinforcement (b= 3.89; 95% CI= 0.96 to 6.82; p= 0.009), self-efficacy (b= 3.04; 95% CI= 0.41 to 5.67; p= 0.024), self-regulation (b= 2.28; 95% CI= 0.02 to 4.54; p= 0.048), outcome expectation (b= 3.56; 95% CI= 0.75 to 6.38; p= 0.013), and a positive attitude (b= 2.86; 95% CI= 0.26 to 5.47; p= 0.031). Posbindu had a contextual effect on tertiary preventive behavior of hypertension with an Intra Class Correlation (ICC) value of 63.05%.Conclusion: Tertiary preventive behavior of hypertension increases with high observational learning, strong role model, strong imitation, high vicarious learning, strong reinforcement, high self-efficacy, high self-regulation, positive outcome expectation, and positive attitude. Posbindu has a contextual effect on tertiary preventive behavior of hypertension.Keywords: tertiary prevention, hypertension, social cognitive theory, multilevel analysisCorrespondence: Very Retnowati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: veryretnowati@gmail.com. Mobile: +6281548592491.Journal of Health Promotion and Behavior (2020), 05(03): 174-186https://doi.org/10.26911/thejhpb.2020.05.03.04